Polyester composite film and preparation method thereof, composite current collector and preparation method thereof, electrode and application thereof

By using photo-strained materials and porous polyester composite films in the composite fluid collecting fluid and combining with the metal layer, the battery is easily broken under the destruction of external forces, solving the problem that the composite fluid collecting fluid cannot be disconnected in time, and improving the safety and stability of the battery.

CN120327063AActive Publication Date: 2025-07-18JIANGSU ENPACK COMPOSITE CURRENT COLLECTORS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510560871.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2025-07-18
Estimated Expiration
2045-04-30

AI Technical Summary

Technical Problem

The existing composite liquid collector cannot be disconnected in time when the external force is damaged, resulting in limited suppression of battery short circuit and thermal runaway.

Method used

A polyester composite film is used as the intermediate layer of the composite fluid collection. The polyester base layer contains photostrained materials, and the surface layer is a polyterephthalate polymer. A porous structure is formed by light irradiation treatment, and a metal layer is deposited on the surface layer to achieve the battery being easily broken under the external force of destruction and inhibit thermal runaway.

Benefits of technology

Effectively suppress battery thermal runaway, improve battery safety performance, reduce elongation, avoid short circuits and intensify heat production, enhance interlayer bonding, and prevent photostrained materials from falling off or frictional damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120327063A_ABST
    Figure CN120327063A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemistry, in particular to a polyester composite film and a preparation method thereof, a composite current collector and a preparation method thereof, and an electrode and application thereof. The polyester composite film comprises a polyester substrate layer, a first surface layer and a second surface layer, wherein the first surface layer and the second surface layer are respectively arranged on two opposite sides of the polyester substrate layer; the polyester substrate layer comprises the following components in parts by weight: 90-99 parts of a polyester material and 1-10 parts of a photoinduced strain material; the components of the first surface layer and the second surface layer comprise a polyterephthalate polymer; the light transmittance of the first surface layer, the light transmittance of the second surface layer and the light transmittance of the polyester material are 92%-99% respectively and independently; the photoinduced strain material comprises one or more of barium titanate ceramic, lead zirconate titanate ceramic, a PI / CNTs photosensitive composite material, a PEEK / anthraquinone photosensitive composite material, an MIL-101 chromium metal organic framework and a UiO-66-NH2 / ZnO composite material. The polyester composite film can be easily broken under high-damage external force such as battery breakdown and battery collision, so that the thermal runaway phenomenon is effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemistry technology, and specifically relates to a polyester composite film and its preparation method, a composite current collector and its preparation method, an electrode and its application. Background Art

[0002] The current collector is one of the important components of a secondary battery, which is beneficial to reducing the internal resistance of the battery, improving the Coulomb efficiency, cycle stability and rate performance of the battery. The main function of the current collector is to collect and output the current generated by the active material and input the electrode current to the active material.

[0003] In order to reduce the weight of the current collector and increase the energy density of the battery, the composite current collector came into being. The composite current collector is a composite material with a "sandwich" structure, where the middle layer is a polymer substrate and a layer of metal material is plated on each of the upper and lower sides. Currently, the polymer substrate of the composite current collector generally uses polyethylene terephthalate (PET) material. The elongation at break of the PET material exceeds 90%, and its relatively high elongation rate causes the composite current collector to be unable to break in time when subjected to a destructive external force, that is, it can still maintain the continuous conduction of the battery under the destructive external force, resulting in phenomena such as battery short circuit and increased heat generation, and thus has limited inhibition of battery thermal runaway. Summary of the Invention

[0004] Based on this, this application provides a polyester composite film and its preparation method, a composite current collector and its preparation method, an electrode and its application. The polyester composite film provided by this application can be used as the middle layer of the composite current collector, and the resulting composite current collector can cause the battery to break more easily under the action of destructive external forces such as battery breakdown and battery collision, thereby effectively inhibiting the battery thermal runaway phenomenon.

[0005] In the first aspect of this application, a polyester composite film is provided, including: a polyester-based bottom layer and a first surface layer and a second surface layer respectively arranged on opposite sides of the polyester-based bottom layer;

[0006] The components of the polyester-based bottom layer, by weight, include: 90 parts to 99 parts of polyester material and 1 part to 10 parts of photoinduced strain material;

[0007] The components of the first surface layer and the second surface layer include polyterephthalate polymers;

[0008] Among them, the light transmittance of the first surface layer, the second surface layer and the polyester material is independently 92% to 99%; the photoinduced strain material includes one or more of barium titanate ceramics, lead zirconate titanate ceramics, PI / CNTs photosensitive composites, PEEK / anthraquinone photosensitive composites, MIL-101 chromium metal-organic frameworks and UiO-66-NH2 / ZnO composites.

[0009] In one embodiment, the first surface layer and the second surface layer are porous structures.

[0010] In one embodiment, based on parts by weight, the raw material components of the first surface layer and the second surface layer each independently include: 5 to 30 parts of an inorganic pore former and 70 to 95 parts of a poly(terephthalate) polymer.

[0011] In one embodiment, based on parts by weight, the poly(terephthalate) polymer includes one or more of polyethylene terephthalate, poly(1,4-cyclohexanedimethylene terephthalate), and polyethylene terephthalate-1,4-cyclohexanedimethylene terephthalate.

[0012] In one embodiment, the inorganic pore former includes one or more of alumina, silica, calcium carbonate, magnesium carbonate, calcium sulfate, barium sulfate, lead sulfate, and zinc oxide.

[0013] In one embodiment, the D50 particle size of the inorganic pore former is 0.01 μm - 2 μm.

[0014] In one embodiment, the thickness ratio of the first surface layer to the polyester-based bottom layer is (1 - 1.5):(3 - 4).

[0015] In one embodiment, the thickness ratio of the second surface layer to the polyester-based bottom layer is (1 - 1.5):(3 - 4).

[0016] In one embodiment, the polyester material includes one or more of polyethylene terephthalate, poly(1,4-cyclohexanedimethylene terephthalate), and polyethylene terephthalate-1,4-cyclohexanedimethylene terephthalate.

[0017] In a second aspect of the present application, there is provided a method for preparing a polyester composite film, the polyester composite film including: a polyester-based bottom layer and a first surface layer and a second surface layer respectively disposed on opposite sides of the polyester-based bottom layer, the preparation method including the following steps:

[0018] Mix the raw materials of the first surface layer, the polyester-based bottom layer, and the second surface layer independently, and after melt pelletizing, respectively prepare a first pellet, a second pellet, and a third pellet;

[0019] Melt-mix and co-extrude the first pellet, the second pellet, and the third pellet respectively, and then perform a stretching treatment to prepare a polyester composite film substrate;

[0020] The components of the polyester base layer include, by weight, 90 to 99 parts of polyester material and 1 to 10 parts of photoinduced strain material; the photoinduced strain material includes one or more of barium titanate ceramics, lead zirconate titanate ceramics, PI / CNTs photosensitive composite materials, PEEK / anthraquinone photosensitive composite materials, MIL-101 chromium metal organic frameworks, and UiO-66-NH2 / ZnO composite materials; the components of the first surface layer and the second surface layer include polyester terephthalate polymers; the transmittance of the first surface layer, the second surface layer, and the polyester material is independently 92% to 99%;

[0021] The polyester composite film substrate is subjected to light irradiation treatment to prepare a polyester composite film. In one embodiment, the raw material components for preparing the first surface layer and the second surface layer independently include: 5 parts to 30 parts of an inorganic pore-forming agent and 70 parts to 95 parts of a polyterephthalate polymer.

[0022] In one embodiment, the preparation method comprises, before the light irradiation treatment, performing an acid wash treatment on the polyester composite film substrate to form a porous structure on the first surface layer and the second surface layer.

[0023] In one embodiment, the pickling step includes: pickling the polyester composite film substrate with an acid elution solvent; wherein the acid elution solvent includes one or more of hydrochloric acid, sulfuric acid, oxalic acid, citric acid, acetic acid and hydrofluoric acid.

[0024] In one of the embodiments, the process parameters of the light irradiation treatment include: the wavelength of the irradiation light is 100nm~1000nm, and the irradiation time is 10s~10min.

[0025] In one embodiment, the photoinduced strain material is barium titanate ceramic, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 240nm~260nm.

[0026] In one embodiment, the photoinduced strain material is lead zirconate titanate ceramic, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 300nm~400nm.

[0027] In one embodiment, the photoinduced strain material is a PI / CNTs photosensitive composite material, and the process parameters of the light irradiation treatment include: the type of irradiation light is infrared light, and the wavelength of the irradiation light is 800nm~1000nm.

[0028] In one embodiment, the photoinduced strain material is a PEEK / anthraquinone photosensitive composite material, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 350 nm to 370 nm.

[0029] In one embodiment, the photoinduced strain material is MIL-101 chromium metal-organic framework, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 340 nm to 365 nm.

[0030] In one embodiment, the photoinduced strain material is UiO-66-NH2 / ZnO composite material, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 300 nm to 400 nm.

[0031] In a third aspect of the present application, a method for preparing a composite current collector is provided, including the following steps:

[0032] Depositing a metal layer on at least one surface of the polyester composite film prepared by the preparation method described in the second aspect of the present application,

[0033] wherein, the time interval between the light irradiation treatment and the deposition of the metal layer is 0.1 minute to 30 minutes.

[0034] In a fourth aspect of the present application, a composite current collector is provided, including the polyester composite film described in any embodiment of the first aspect of the present application and a metal layer provided on at least one surface of the polyester composite film.

[0035] In one embodiment, the material of the metal layer includes one or more of aluminum and aluminum alloy.

[0036] In one embodiment, the thickness of the metal layer is 0.8 mm to 1.2 mm.

[0037] In a fifth aspect of the present application, an electrode is provided, including the composite current collector described in the fourth aspect of the present application or the composite current collector prepared by the preparation method described in the third aspect of the present application.

[0038] In a sixth aspect of the present application, a battery is provided, including the electrode described in the fifth aspect of the present application.

[0039] The polyester composite film provided by the present application has at least the following beneficial effects:

[0040] The polyester composite film provided by this application includes a polyester-based bottom layer, a first surface layer and a second surface layer respectively disposed on opposite sides of the polyester-based bottom layer. Among them, the components of the polyester-based bottom layer include a specific type of photo-induced strain material. The above-mentioned photo-induced strain material and a specific weight fraction of polyester material cooperate with each other, and under the condition that the first surface layer, the second surface layer and the polyester material have light transmittance, the photo-induced strain material can change the stress distribution uniformity of the polyester-based bottom layer under light irradiation, so that the local stress of the polyester-based bottom layer is concentrated, and then the overall elongation rate of the polyester composite film can be reduced. Therefore, when the battery is subjected to external forces such as battery breakdown and battery collision, the above-mentioned polyester composite film can be easily broken, avoiding phenomena such as battery short circuit and increased heat generation, and then effectively suppressing the battery thermal runaway phenomenon and significantly improving the safety performance of the battery.

[0041] The first surface layer and the second surface layer can prevent the photo-induced strain material from being exposed on the surface layer of the polyester composite film, thereby preventing the photo-induced strain material from falling off or the film surface damage caused by the friction of the photo-induced strain material on the film surface after the polyester composite film is wound. And the components of the first surface layer and the second surface layer include polyterephthalate polymers, which have excellent compatibility with the polyester-based bottom layer, and then can effectively enhance the interlayer adhesion force and avoid the delamination phenomenon of the polyester composite film when the photo-induced strain material undergoes volume change. Brief Description of the Drawings

[0042] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required to be used in the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0043] Figure 1 It is a schematic structural diagram of the polyester composite film provided by an example of this application.

[0044] In the figure, 10 is the polyester composite film; 100 is the polyester-based bottom layer; 200 is the first surface layer; 300 is the second surface layer. Detailed Embodiments

[0045] The following further describes the polyester composite film of this application, its preparation method, the composite current collector and its preparation method, the electrode and its application in combination with specific embodiments. This application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosed content of this application more thorough and comprehensive.

[0046] Refer to Figure 1In a first aspect of the present application, a polyester composite film 10 is provided, comprising: a polyester base layer 100 and a first surface layer 200 and a second surface layer 300 respectively disposed on opposite sides of the polyester base layer 100 .

[0047] In one example, the components of the polyester base layer 100 include, by weight, 90 to 99 parts of polyester material and 1 to 10 parts of photoinduced strain material.

[0048] In one example, the photoinduced strain material includes one or more of barium titanate ceramics, lead zirconate titanate ceramics, PI / CNTs photosensitive composite materials, PEEK / anthraquinone photosensitive composite materials, MIL-101 chromium metal organic frameworks, and UiO-66-NH2 / ZnO composite materials.

[0049] The components of the polyester base layer include a specific type of photoinduced strain material. The photoinduced strain material and the polyester material of a specific weight fraction cooperate with each other to change the uniformity of stress distribution of the polyester base layer, thereby concentrating the local stress of the polyester base layer, and then reducing the overall elongation of the polyester composite film. Barium titanate ceramics are ceramic materials with barium titanate (BaTiO3) or its solid solution as the main crystal phase, and have an ABO3 perovskite structure. Lead zirconate titanate ceramics are composed of lead, zirconium, titanium, oxygen and other elements, and also have a perovskite structure. Light irradiation can cause changes in the internal electronic structure of the above-mentioned ceramic materials, resulting in the displacement of ions in their crystal structure. At the same time, light irradiation may cause defects such as oxygen vacancies in the above-mentioned materials, thereby affecting the charge distribution and stress state inside the material, causing the volume of the material to change.

[0050] PI / CNTs photosensitive composite material is a composite material composed of polyimide (PI) and carbon nanotubes (CNTs). It is photosensitivity and will undergo specific physical and chemical changes under light irradiation. After the photosensitive groups in the PI molecular chain absorb photon energy, they undergo cross-linking reactions or conformational changes, which change the arrangement and interaction of the molecular chains, thereby causing changes in the microstructure of the material. On the other hand, CNTs have good photothermal conversion properties. After absorbing light, they convert light energy into heat energy, causing the local temperature of the material to rise, resulting in thermal expansion, and then causing the volume of the polyester base layer to change. Therefore, the above materials cooperate with each other, and after light irradiation, the PI / CNTs photosensitive composite material undergoes a significant volume change, which in turn affects the overall stress distribution of the polyester composite film and affects the elongation at break of the polyester composite film.

[0051] The PEEK / anthraquinone photosensitive composite material is a new composite material composed of polyetheretherketone (PEEK) and anthraquinone photosensitizer. Under light irradiation, anthraquinone will undergo a photochemical reaction, generating photogenerated carriers and free radicals, etc. These changes will cause changes in the charge distribution and chemical potential inside the material, and then lead to changes in the conformation of molecular chains and the intermolecular interaction force. At the same time, PEEK may also undergo thermal expansion due to heat absorption under light irradiation, resulting in volume changes in the PEEK / anthraquinone photosensitive composite material under light irradiation.

[0052] MIL-101 chromium metal-organic framework is a metal-organic framework material composed of metal chromium ions and terephthalic acid ligands. Light irradiation will cause processes such as electron transitions in the metal ions or ligands in the material, resulting in changes in the nature and strength of its chemical bonds, and then causing adjustments to the crystal structure. In addition, the thermal effect inside the material caused by light irradiation makes the material undergo volume changes.

[0053] The UiO-66-NH2 / ZnO composite material is a composite material composed of the metal-organic framework UiO-66-NH2 and nano-zinc oxide (ZnO). Light irradiation will cause UiO-66-NH2 and ZnO to generate photogenerated carriers, resulting in changes in the internal charge distribution of the material and generating internal stress.

[0054] Therefore, the above materials will undergo volume or stress changes under light irradiation, which will affect the overall stress distribution of the polyester-based film, and then affect the elongation at break of the polyester-based film. It can be understood that the weight parts of the polyester material can be selected from any value between 1 part and 10 parts. For example, the weight parts of the photo-induced strain material include but are not limited to 1 part, 3 parts, 5 parts, 7 parts, 9 parts or 10 parts, or within the range formed by any two of the above point values as end point values. The weight parts of the polyester material can be selected from any value between 90 parts and 99 parts. For example, the weight parts of the polyester material include but are not limited to 90 parts, 93 parts, 95 parts, 97 parts, 98 parts or 99 parts. Limiting the components of the polyester-based bottom layer within the above range can not only ensure that the photo-induced strain material exerts sufficient volume and stress changes, but also retain the tensile strength of the polyester composite film. If the content of the photo-induced strain material is too low, the volume and stress changes exerted will be limited, that is, the influence on the elongation at break of the polyester composite film is limited. If the content of the photo-induced strain material is too high, it will lead to a decrease in the film-forming property of the polyester composite film and a decrease in the strength of the polyester composite film.

[0055] In one example, the polyester material includes one or more of polyethylene terephthalate, poly(1,4-cyclohexanedimethylene terephthalate) and poly(ethylene terephthalate-co-1,4-cyclohexanedimethylene terephthalate).

[0056] In one example, the components of the first surface layer and the second surface layer include poly(terephthalate) polymers.

[0057] The arrangement of the first surface layer and the second surface layer can prevent the photoinduced strain material from being exposed on the surface layer of the polyester composite film, thereby avoiding the shedding of the photoinduced strain material or the damage to the film surface caused by the friction of the photoinduced strain material on the film surface after the polyester composite film is wound. Moreover, the components of the first surface layer and the second surface layer include poly(terephthalate) polymers, which have excellent compatibility with the polyester-based bottom layer, and thus can effectively enhance the interfacial adhesion force and prevent delamination of the polyester composite film when the photoinduced strain material undergoes volume changes.

[0058] In one example, the light transmittance of the first surface layer, the second surface layer, and the polyester material is independently 92% - 99%. The high light transmittance of the first surface layer, the second surface layer, and the polyester material enables the photoinduced strain material to be fully irradiated by light, ensuring volume or stress changes. It can be understood that the light transmittance of the first surface layer, the second surface layer, and the polyester material independently includes, but is not limited to, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%. The light transmittance of the first surface layer, the second surface layer, and the polyester material can be adjusted by controlling process parameters such as the crystallinity of the polymer material, and the forming temperature, pressure, and speed during film drawing.

[0059] In one example, the first surface layer and the second surface layer are porous structures. The components of the first surface layer and the second surface layer include poly(terephthalate) polymers.

[0060] In one example, the porous structures of the first surface layer and the second surface layer are obtained by pickling with an inorganic pore-forming agent.

[0061] The components of the first surface layer and the second surface layer include poly(terephthalate) polymers, which have excellent compatibility with the polyester-based bottom layer, and thus can effectively enhance the interfacial adhesion force and prevent delamination. At the same time, the porous structures of the first surface layer and the second surface layer increase the surface roughness of the polyester composite film, thereby increasing its adhesion force with the metal layer. In addition, the porous structures of the first surface layer and the second surface layer destroy the continuity and uniformity of the material. When the battery is subjected to external destructive forces, the stress values in the stress concentration regions of the first surface layer and the second surface layer are much higher than the average stress, which also makes the material unable to further undergo large plastic deformation and reduces the elongation rate. At the same time, the porous structures of the first surface layer and the second surface layer can reduce energy loss during the light irradiation process, enabling the photoinduced strain material to be fully irradiated by light, ensuring volume or stress changes. And when the photoinduced strain material undergoes volume changes, the porous structures absorb a certain amount of deformation, preventing the first surface layer and the second surface layer from separating from the polyester substrate.

[0062] It should be noted that since the photoinduced strain material is disposed in the polyester substrate, the acid pickling liquid reacts less with the photoinduced strain material during the acid pickling process, avoiding the influence of acid pickling on the effect of the photoinduced strain material.

[0063] In one example, by weight, the raw material components of the first surface layer and the second surface layer each independently include: 5 parts to 30 parts of an inorganic pore former and 70 parts to 95 parts of a polyterephthalate polymer.

[0064] The weight fraction of the inorganic pore former plays an important role in ensuring the porosity of the porous structure in the first surface layer and the second surface layer. The addition of the inorganic pore former can provide anchor points for the formation of the porous structure in the first surface layer and the second surface layer, and can affect the pore distribution density and pore size of the porous structure in the first surface layer and the second surface layer.

[0065] Exemplarily, the weight fraction of the inorganic pore former includes but is not limited to 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, or within the range formed by any two of the above point values as end point values. The weight fraction of the polyterephthalate polymer includes but is not limited to 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts, 88 parts, 90 parts, 92 parts, 95 parts, 98 parts or 100 parts, or within the range formed by any two of the above point values as end point values. Limiting the weight fraction of the raw material components of the first surface layer and the second surface layer can ensure both the pore distribution density of the first surface layer and the second surface layer and their film-forming properties. If the content of the inorganic pore former is slightly less, the pore distribution density of the first surface layer and the second surface layer will be slightly smaller, and thus the influence on the elongation at break of the overall polyester composite film is limited. If the content of the inorganic pore former is slightly more, the film-forming property of the first surface layer and the second surface layer will decrease, increasing the risk of film breakage.

[0066] In one example, the inorganic pore former includes one or more of alumina, silica, calcium carbonate, magnesium carbonate, calcium sulfate, barium sulfate, lead sulfate and zinc oxide.

[0067] In one example, the D50 particle size of the inorganic pore former is 0.01 μm to 2 μm. When the D50 particle size of the inorganic pore former is within the above range, it is helpful to form pores with uniform pore size and regular shape in the first surface layer and the second surface layer.

[0068] In one example, by weight, the polyterephthalate polymer includes one or more of polyethylene terephthalate, poly(1,4-cyclohexanedimethylene terephthalate) and polyethylene terephthalate-1,4-cyclohexanedimethylene ester.

[0069] In one example, the thickness ratio of the first surface layer to the polyester-based bottom layer is (1~1.5):(3~4). Further, the thickness ratio of the first surface layer to the polyester-based bottom layer includes, but is not limited to, 1:3, 1:3.5, 1:4, 1.2:3, 1.2:3.5, 1.2:4, 1.5:3, 1.5:3.5, or 1.5:4, or within the range formed by any two of the above point values as the end values.

[0070] In one example, the thickness ratio of the second surface layer to the polyester-based bottom layer is (1~1.5):(3~4). Further, the thickness ratio of the second surface layer to the polyester-based bottom layer includes, but is not limited to, 1:3, 1:3.5, 1:4, 1.2:3, 1.2:3.5, 1.2:4, 1.5:3, 1.5:3.5, or 1.5:4, or within the range formed by any two of the above point values as the end values.

[0071] When the thickness ratios of the first surface layer to the polyester-based bottom layer and the second surface layer to the polyester-based bottom layer are within the above ranges, it is beneficial to exert the synergistic effect between the polyester-based bottom layer and the surface layers, form a reasonable stress distribution between them, not only ensure the ability of the polyester composite film to resist tensile failure, but also reduce its elongation at break.

[0072] In one example, the thickness of the polyester-based bottom layer is 3μm~15μm. Limiting the thickness of the polyester-based bottom layer within the above range can, on the one hand, endow the composite current collector with ideal mechanical strength and flexibility, effectively avoid conditions such as rupture and wrinkles, and greatly enhance the structural stability; on the other hand, it is beneficial to achieve the lightweight design goal, reduce the material cost, and improve the battery energy density.

[0073] In the second aspect of the present application, there is provided a method for preparing the polyester composite film according to any one of the examples in the first aspect of the present application, including the following steps:

[0074] S10: Independently mix the raw materials of the first surface layer, the polyester-based bottom layer, and the second surface layer, and after melt pelletizing treatment, respectively prepare the first pellet, the second pellet, and the third pellet.

[0075] S20: Melt and mix the first pellet, the second pellet, and the third pellet respectively, co-extrude them, and then perform a stretching treatment to prepare a polyester composite film substrate; wherein, the polyester composite film substrate includes a polyester-based bottom layer, a first surface layer, and a second surface layer. The first surface layer and the second surface layer are located on opposite sides of the polyester-based bottom layer.

[0076] S30: Perform a light irradiation treatment on the polyester composite film substrate to form a porous structure on the first surface layer and the second surface layer, and prepare a polyester composite film.

[0077] Understandably, the polyester composite film includes: a polyester-based bottom layer, and a first surface layer and a second surface layer respectively disposed on opposite sides of the polyester-based bottom layer.

[0078] In one example, before the light irradiation treatment, the preparation method includes: pickling the polyester composite film substrate to form a porous structure on the first surface layer and the second surface layer.

[0079] Further, the pickling step includes: pickling the polyester composite film substrate with an acid elution solvent.

[0080] Among them, the acid elution solvent includes one or more of hydrochloric acid, sulfuric acid, oxalic acid, citric acid, acetic acid, and hydrofluoric acid.

[0081] The above-mentioned types of acid elution solvents can not only clean the inorganic pore-forming agents on the surfaces of the first surface layer and the second surface layer, but also penetrate into the interiors of the first surface layer and the second surface layer to wash away the internal inorganic pore-forming agents, thereby forming pores within a relatively short pickling treatment time and reducing the impact of long-term contact with the acid elution solvent on the polyester composite film. The formation of these pores can effectively reduce the elongation rate of the polyester composite film while retaining its tensile strength. In addition, the presence of the pores can also increase the surface roughness of the polyester-based film and enhance the bonding force with the metal layer.

[0082] In one example, the first surface layer and the second surface layer do not include photo-induced strain materials. It is found in this application that when a photo-induced strain material is added to the first surface layer or the second surface layer, its compatibility with the inorganic pore-forming agent is slightly poor, which will affect the film formation of the first surface layer and the second surface layer. In addition, since the first surface layer or the second surface layer will undergo a pickling step, if the photo-induced strain material is disposed on the first surface and the second surface layer, the acid elution solvent will react with the photo-induced strain material, affecting the effect of the photo-induced strain material. Setting the photo-induced strain material in the polyester-based bottom layer can effectively avoid the impact of pickling on the photo-induced strain material.

[0083] In one example, the process parameters of the light irradiation treatment include: the irradiation light wavelength is 100 nm to 1000 nm, and the irradiation time is 10 s to 10 min. The irradiation time plays an important role in ensuring the photo-induced strain effect and avoiding thermal damage to the polyester composite film. If the light irradiation time is slightly short, the volume change and local strain of the photo-induced strain material are slightly low, and its influence on the elongation rate of the polyester composite film is limited. If the light irradiation time is slightly long, the thermal damage to the polyester composite film is slightly high, affecting the strength of the polyester composite film and the coating effect of the subsequent metal layer.

[0084] The light irradiation treatment can cause volume or stress changes in the photo-induced strain material in the polyester-based substrate, thereby affecting the overall stress distribution of the polyester composite film to ensure an appropriate elongation at break of the polyester composite film.

[0085] This application finds that different types of photo-induced strain materials have different optical absorption characteristics and energy level structures. Only by selecting the appropriate irradiation light and corresponding wavelength that match them can the photo-induced strain materials be effectively excited to produce the expected strain response.

[0086] Exemplarily, the photo-induced strain material is barium titanate ceramic, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 240 nm to 260 nm.

[0087] Exemplarily, the photo-induced strain material is lead zirconate titanate ceramic, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 300 nm to 400 nm.

[0088] Exemplarily, the photo-induced strain material is PI / CNTs photosensitive composite material, and the process parameters of the light irradiation treatment include: the type of irradiation light is infrared light, and the wavelength of the irradiation light is 800 nm to 1000 nm.

[0089] Exemplarily, the photo-induced strain material is PEEK / anthraquinone photosensitive composite material, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 350 nm to 370 nm.

[0090] Exemplarily, the photo-induced strain material is MIL-101 chromium metal-organic framework, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 340 nm to 365 nm.

[0091] Exemplarily, the photo-induced strain material is UiO-66-NH2 / ZnO composite material, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 300 nm to 400 nm.

[0092] In the third aspect of this application, a composite current collector is provided, which includes the polyester composite film according to any one of the first aspect of this application and a metal layer disposed on at least one surface of the polyester composite film.

[0093] In one example, the material of the metal layer includes one or more of aluminum and aluminum alloys.

[0094] It is found in this application that internal short circuits in the anode material - cathode material and the cathode aluminum current collector - cathode material in the types of battery thermal runaway are all directly related to the cathode aluminum current collector. The elongation rate of pure aluminum material is 10% - 30%, and the elongation rate of PET material generally exceeds 90%. Therefore, the elongation at break of the composite current collector aluminum foil as a whole is mainly determined by the PET film material. However, the excessive elongation at break makes the composite aluminum foil unable to break immediately when subjected to external force damage. The polyester composite film and the composite current collector provided in this application can reduce its elongation rate, thereby preventing the occurrence of battery thermal runaway.

[0095] In one example, the thickness of the metal layer is 0.8 µm - 1.2 µm. This thickness range can ensure that the metal layer has good electrical conductivity, effectively reduce the internal resistance of the battery, and improve the charge and discharge efficiency and performance stability of the battery.

[0096] This application also provides a preparation method of a composite current collector, including the following steps:

[0097] Deposit a metal layer on at least one surface of the polyester composite film prepared by the preparation method described in any example of the second aspect of this application. Among them, the time interval between the light irradiation treatment and the deposition of the metal layer is 0.1 minute - 30 minutes. Further, the method of depositing the metal layer includes but is not limited to vacuum evaporation.

[0098] After the polyester composite film is irradiated with light, the photoinduced strain material in the polyester base layer will have volume changes and local strains, and the stress changes will cause small deformations and wrinkles to form on the surface of the polyester composite film. It is found in this application that when the above-mentioned polyester composite film is subjected to vacuum evaporation, the deformations and wrinkles formed on the surface of the polyester composite film will be flattened under the action of the high temperature in the evaporation chamber and the flattening roller, thereby effectively reducing the influence on the adhesion of the metal layer.

[0099] In addition, the time interval between the light irradiation treatment and the deposition of the metal layer is set between 0.1 minute and 30 minutes. That is, the polyester composite film after the light irradiation treatment can directly enter the process of depositing the metal layer without an additional winding step for the polyester composite film. This effectively avoids the problem that the tiny strains caused by the light irradiation treatment of the photoinduced strain material inside the polyester composite film accumulate to form wrinkles and deformations under the action of the winding tension pressure and become dead wrinkles under the long-term winding pressure.

[0100] Further, in the preparation method of the composite current collector in this application, the polyester composite film after the light irradiation treatment is deposited with a metal layer, that is, the step of light irradiation treatment is before and the step of preparing the metal layer is after. This also effectively avoids the problem that the metal layer on the surface of the polyester composite film is opaque and will reflect most of the ultraviolet / infrared light and cannot induce photoinduced strain.

[0101] In one example, the material of the metal layer is aluminum.

[0102] Exemplarily, the vacuum evaporation equipment includes, but is not limited to, an evaporation boat and a wire feeding system. More specifically, the vacuum evaporation equipment consists of 72 groups of evaporation boats. The wire feeding system sends the aluminum wire above the evaporation boat. The heat generated by heating the evaporation boat melts the aluminum wire. After the molten aluminum drips onto the evaporation boat, it further evaporates to form a gas, which eventually deposits on the polyester composite film. Exemplarily, the diameter of the aluminum wire is 1.5 mm to 2.5 mm.

[0103] In one example, the process parameters of the vacuum evaporation include: the wire feeding speed of the wire feeding system is 400 mm / min to 500 mm / min. Exemplarily, the wire feeding speed of the wire feeding system includes, but is not limited to, 400 mm / min, 410 mm / min, 420 mm / min, 430 mm / min, 440 mm / min, 450 mm / min, 460 mm / min, 470 mm / min, 480 mm / min, 490 mm / min or 500 mm / min, or any range formed by any two of the above point values as endpoint values.

[0104] In one example, the evaporation rate of the vacuum evaporation is 10 m / min to 20 m / min. The evaporation rate within the above range can ensure production efficiency while ensuring the yield of the evaporated product and avoiding excessive production costs. Exemplarily, the evaporation rate includes, but is not limited to, 10 m / min, 12 m / min, 15 m / min, 18 m / min or 20 m / min, or any range formed by any two of the above point values as endpoint values.

[0105] In one example, the evaporation power of the vacuum evaporation is 7 kW to 12 kW. The evaporation power of the vacuum evaporation is generally about 5 kW. The evaporation power in this application within the above range can ensure sufficient heat treatment effect. If the evaporation power is too large, it will cause excessive thermal damage to the polymer composite film, and its tensile strength will be significantly reduced. If the evaporation power is too small, it will cause insufficient crystallinity of the polymer composite film, resulting in an insignificant decrease in its elongation. Exemplarily, the evaporation power of the vacuum evaporation includes, but is not limited to, 7 kW, 7.5 kW, 8 kW, 8.5 kW, 9 kW, 9.5 kW, 10 kW, 10.5 kW, 11 kW, 11.5 kW or 12 kW, or any range formed by any two of the above point values.

[0106] In one example, the temperature of the main roller in vacuum evaporation is -20°C to 0°C. The temperature of the main roller in evaporation within the above range synergizes with the evaporation power to ensure sufficient heat ironing effect. Exemplarily, the temperature of the main roller in vacuum evaporation includes but is not limited to -20°C, -18°C, -16°C, -14°C, -12°C, -10°C, -8°C, -6°C, -4°C, -2°C or 0°C, or within the range formed by any two of the above point values. If the temperature of the main roller in evaporation is too low, the cooling effect on the polyester composite film is obvious, which will cause it to fail to achieve sufficient heat ironing and flattening effect. At this time, the deformation and wrinkles formed due to uneven stress distribution caused by photoinduced strain cannot be fully ironed and flattened, which will affect the appearance quality of the composite aluminum foil. If the temperature of the main roller in evaporation is too high, the heat cannot be dissipated in time, which will cause excessive thermal damage to the polyester composite film, and its tensile strength will be significantly reduced, and at the same time, the appearance deterioration will be aggravated.

[0107] In one example, the winding tension and unwinding tension in vacuum evaporation are each independently 100N to 300N. The winding and unwinding tensions within the above range can not only accelerate and optimize the heat treatment effect, but also ensure good winding effect and appearance quality. Exemplarily, the winding tension and unwinding tension in vacuum evaporation each independently include but are not limited to 100N, 110N, 120N, 150N, 180N, 200N, 220N, 250N, 270N, 280N or 300N, or within the range formed by any two of the above point values as the end point values. It is found in this application that too large or too small winding tension will affect the heat ironing and flattening effect on the polyester composite film.

[0108] In one example, the distance between the evaporation boat and the polymer composite film in vacuum evaporation is 250mm to 350mm. The distance between the evaporation boat and the polymer composite film within the above range can not only ensure the heat treatment effect, but also prevent excessive thermal damage to the polymer composite film. Exemplarily, the distance between the evaporation boat and the polymer composite film in vacuum evaporation includes but is not limited to 250mm, 270mm, 290mm, 310mm, 330mm or 350mm, or within the range formed by any two of the above point values as the end point values.

[0109] In the fifth aspect of this application, an electrode is provided, which includes the composite current collector described in the fourth aspect of this application or the composite current collector prepared by the preparation method described in the third aspect of this application.

[0110] In the sixth aspect of this application, a battery is provided, which includes the electrode described in the fifth aspect of this application.

[0111] In the seventh aspect of this application, an electrical device is provided, which includes the battery described in the fifth aspect.

[0112] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values of the embodiments below.

[0113] Example 1

[0114] Example 1 of the present application provides a polyester composite film and a preparation method thereof, a composite current collector and a preparation method thereof.

[0115] Polyester composite film:

[0116] (1) Forming a polyester composite film substrate: The polyester composite film substrate includes a polyester base layer and a first surface layer and a second surface layer respectively disposed on opposite sides of the polyester base layer. The raw material components of the polyester base layer include, by weight, 95 parts of PET material and 5 parts of photoinduced strain material (barium titanate ceramic). The raw material components of the first surface layer and the second surface layer include, by weight, 20 parts of inorganic pore-forming agent (D50 particle size is 1 μm) calcium sulfate and 80 parts of PET material. The thickness of the polyester base layer is 6 μm; the thickness ratio of the first surface layer to the polyester base layer is 1.0:4.0, and the thickness ratio of the second surface layer to the polyester base layer is 1.0:4.0.

[0117] (2) The polyester composite film substrate is pickled with hydrochloric acid to remove the inorganic pore-forming agent, so that the first surface layer and the second surface layer form a porous structure; then the polyester composite film substrate is subjected to light irradiation treatment: the irradiation light type is ultraviolet light, the irradiation light wavelength is 250nm, and the irradiation time is 2min, so that the polyester base layer undergoes strain or volume change, and a polyester composite film is prepared. Among them, the light transmittance of the PET material, the first surface layer, and the second surface layer is 96%.

[0118] Composite current collector:

[0119] Using 72 groups of evaporation boats and aluminum wires with a diameter of 2 mm, the aluminum wires were vacuum evaporated onto the opposite side surfaces of the polyester composite film to prepare the first metal layer and the second metal layer respectively (the time interval between the formation of the first metal layer and the second metal layer and the light irradiation treatment was 15 minutes), the first metal layer was arranged on the side of the first surface layer away from the polyester base layer, the second metal layer was arranged on the side of the second surface layer away from the polyester base layer, and the thickness of the first metal layer and the second metal layer was 1 μm; a composite current collector was obtained.

[0120] Among them, the process parameters of vacuum evaporation coating include: the wire feeding speed of aluminum wire is 450 mm / min, the evaporation rate is 15 m / min, the evaporation power is 8 kW, the temperature of the main roller for evaporation coating is -10 °C, the tension of the winding and unwinding for evaporation coating is 200 N, and the distance between the evaporation boat for vacuum evaporation coating and the polymer composite film is 300 mm.

[0121] Example 2

[0122] Example 2 is basically the same as Example 1. The main difference is that the type of photoinduced strain material added in Example 2 is MIL-101 chromium metal-organic framework.

[0123] The type of irradiation light is ultraviolet light, the wavelength of the irradiation light is 365 nm, and the irradiation time is 2 min.

[0124] Example 3

[0125] Example 3 is basically the same as Example 1. The main difference is that the type of photoinduced strain material added in Example 3 is PEEK / anthraquinone photosensitive composite material.

[0126] The type of irradiation light is ultraviolet light, the wavelength of the irradiation light is 350 nm, and the irradiation time is 5 min.

[0127] Example 4

[0128] Example 4 is basically the same as Example 1. The main difference is that the type of inorganic pore-forming agent added in Example 4 is calcium carbonate.

[0129] Example 5

[0130] Example 5 is basically the same as Example 1. The main difference is that the raw material components of the first surface layer and the second surface layer, by weight, include: 5 parts of inorganic pore-forming agent (D50 particle size is 0.01 μm) and 95 parts of PET material.

[0131] Example 6

[0132] Example 6 is basically the same as Example 1. The main difference is that the raw material components of the polyester-based bottom layer, by weight, include: 99 parts of PET material and 1 part of photoinduced strain material (barium titanate ceramic).

[0133] Example 7

[0134] Example 7 is basically the same as Example 1. The main difference is that the raw material components of the polyester-based bottom layer, by weight, include: 90 parts of PET material and 10 parts of photoinduced strain material (barium titanate ceramic).

[0135] Example 8

[0136] Example 8 is basically the same as Example 2, and the main difference is that the wavelength of the irradiation light is 300 nm.

[0137] Example 9

[0138] Example 9 is basically the same as Example 1, and the main difference is that the raw material components of the first surface layer and the second surface layer in Example 9 do not include inorganic pore-forming agents.

[0139] Example 10

[0140] Example 10 is basically the same as Example 1, and the main difference is that the light transmittance of the PET material, the first surface layer, and the second surface layer in Example 10 is 99%.

[0141] Example 11

[0142] Example 11 is basically the same as Example 1, and the main difference is that the light transmittance of the PET material, the first surface layer, and the second surface layer in Example 10 is 92%.

[0143] Comparative Example 1

[0144] Polymer substrate: The material of the polymer substrate is a PET layer with a thickness of 6 μm.

[0145] Composite current collector and its preparation method: 72 evaporation boats and aluminum wires with a diameter of 2 mm are used. The aluminum wires are vacuum-evaporated on the opposite two surface sides of the polymer substrate to respectively prepare a first metal layer and a second metal layer, and the thicknesses of the first metal layer and the second metal layer are 1 μm; a composite current collector is obtained.

[0146] Among them, the process parameters of the vacuum evaporation include: the wire feeding speed of the aluminum wire is 450 mm / min, the evaporation rate is 15 m / min, the evaporation power is 8 kW, the temperature of the main evaporation roller is -10 °C, the winding and unwinding tension of the evaporation is 200 N, and the distance between the evaporation boat of the vacuum evaporation and the polymer composite film is 300 mm.

[0147] Comparative Example 2

[0148] Comparative Example 2 is basically the same as Example 1, and the main difference is that the raw material components of the polyester-based bottom layer in Comparative Example 2 do not include photo-induced strain materials.

[0149] Performance test:

[0150] Mechanical property test of the composite current collector

[0151] Tensile strength and elongation at break tests were carried out on the composite current collectors prepared in the examples and comparative examples. The composite current collectors to be tested were cut into test specimens using a strip cutter. For each group of samples in the examples, 10 test specimens were cut, with a width of 15 mm and a length of 150 mm. The tensile rate was 100 mm / min, the distance between the tensile chucks was 100 mm, and the tensile strength and elongation at break data in the MD direction were tested and averaged. The test data are shown in Table 1.

[0152] Table 1

[0153]

[0154] Battery collision safety performance test

[0155] The cathode slurry was obtained by fully stirring and mixing ternary active material NCM811, conductive carbon black, and binder PVDF in a weight ratio of 93:2:5 in NMP. The cathode slurry was coated on the current collector samples of the examples or comparative examples, dried, rolled, and then die-cut to obtain cathode plates.

[0156] The anode slurry was obtained by fully stirring and mixing artificial graphite as the anode active material, binder SBR, dispersant CMC, and conductive carbon black in a weight ratio of 95.5:2.3:1.5:0.7 in water. The anode slurry was coated on copper foil, dried, rolled, and then die-cut to obtain anode plates.

[0157] The above-mentioned cathode plates, separator (PE film), and anode plates were stacked in sequence, wound to obtain a battery core, placed in a battery case, filled with electrolyte (lithium salt LiPF6, concentration 1 mol / L, carbonate solvent), and then encapsulated to obtain battery samples.

[0158] The battery samples obtained from the composite current collectors prepared in the examples and comparative examples were respectively subjected to collision safety performance tests.

[0159] (1) Battery pretreatment

[0160] The encapsulated battery samples were charged to the rated capacity (SOC = 100%) and left standing for more than 4 hours to eliminate the polarization effect. Temperature measurement holes were reserved during battery production, and a micro-thermocouple was placed for temperature measurement.

[0161] (2)Battery fixation

[0162] The battery samples were fixed on the test bench, clamped in a three-point manner, and a metal pendulum was installed on the test bench to ensure that the battery axis was completely perpendicular to the movement trajectory of the pendulum. The impact center point was marked on the front of the battery.

[0163] (3)Collision test

[0164] Release the pendulum so that it impacts the center point of the battery front three times in free fall, and record the temperature value inside the battery sample 10 minutes after the impact. The test data is shown in Table 2.

[0165] Table 2

[0166]

[0167] From the test results in Table 1 to Table 2, it can be seen that Examples 1 to 3 are basically the same. The main difference is that the types of photoinduced strain materials are different. Among them, the MIL-101 chromium metal-organic framework photoinduced strain material in Example 2 has the lowest cell temperature in the collision test. Therefore, it can more effectively suppress the thermal runaway phenomenon.

[0168] Example 1 and Example 4 are basically the same. The main difference is that the types of inorganic pore formers are different; from the test results in Table 1 and Table 2, the calcium sulfate inorganic pore former in Example 1 is more easily removed by pickling to enrich the porous structures of the first surface layer and the second surface layer, thereby effectively suppressing battery thermal runaway and improving battery safety performance.

[0169] Example 1 and Example 5 are basically the same. The main difference is that the weight parts of the inorganic pore former are different. According to the comparison, when the mass parts of the inorganic pore former and the PET material in Example 1 are 20 parts and 80 parts respectively, its inhibitory effect on battery thermal runaway can be excellent.

[0170] Example 1, Example 6 and Example 7 are basically the same. The main difference is that the weight parts of the photoinduced strain material are different. According to the comparison, when the mass parts of the PET material and the photoinduced strain material in Example 7 are 90 parts and 10 parts respectively, its inhibitory effect on battery thermal runaway can be excellent.

[0171] Example 2 and Example 8 are basically the same. The main difference is that the irradiation light wavelength is different. From the above comparison, it can be seen that the photoirradiation parameters of the photoinduced strain material play an important role in reducing the elongation at break of the polyester composite film. The preferred irradiation light wavelength of MIL-101 chromium metal-organic framework is 340nm - 365nm.

[0172] Example 1 and Example 9 are basically the same. The main difference is that Example 9 does not contain a pore former. At this time, since the first surface layer and the second surface layer do not form a porous structure, its inhibition of the thermal runaway phenomenon is relatively limited.

[0173] Example 1, Example 10, and Example 11 are basically the same, and the main difference lies in that the light transmittance of the PET material, the first surface layer, and the second surface layer is different in each example. When the light transmittance of the PET material, the first surface layer, and the second surface layer in Example 10 is 99%, the photoinduced strain material can more significantly change the stress distribution uniformity of the polyester-based substrate under light irradiation, and thus can more effectively inhibit the battery thermal runaway phenomenon and ensure the safety performance of the battery.

[0174] Neither Comparative Example 1 nor Comparative Example 2 selected the polyester composite film of the present application as the inner layer of the composite current collector. Therefore, their elongation at break and the cell temperature are relatively high, and the thermal runaway phenomenon under collision conditions cannot be inhibited.

[0175] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as falling within the scope described in this specification.

[0176] The above-described embodiments only represent several implementation manners of the present application, which are convenient for understanding the technical solutions of the present application specifically and in detail, but should not be construed as a limitation on the protection scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present application, several modifications and improvements can still be made, and these all belong to the protection scope of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning, or limited experiments based on the technical solutions provided in the present application are all within the protection scope of the appended claims of the present application. Therefore, the protection scope of the patent of the present application should be subject to the content of the appended claims, and the specification can be used to interpret the content of the claims.

Claims

1. A polyester composite film, characterized in that, include: A polyester base layer and a first surface layer and a second surface layer respectively disposed on opposite sides of the polyester base layer; The components of the polyester base layer include, by weight: 90 to 99 parts of polyester material and 1 to 10 parts of photoinduced strain material; The components of the first surface layer and the second surface layer include a polyterephthalate polymer; Among them, the transmittance of the first surface layer, the second surface layer and the polyester material is independently 92%~99%; the photoinduced strain material includes one or more of barium titanate ceramics, lead zirconate titanate ceramics, PI / CNTs photosensitive composite materials, PEEK / anthraquinone photosensitive composite materials, MIL-101 chromium metal organic framework and UiO-66-NH2 / ZnO composite materials.

2. The polyester composite film according to claim 1, wherein The first surface layer and the second surface layer are porous structures.

3. The polyester composite film according to claim 2, wherein, In parts by weight, the raw material components for preparing the first surface layer and the second surface layer independently include: 5 to 30 parts of an inorganic pore-forming agent and 70 to 95 parts of a polyterephthalate polymer.

4. The polyester composite film according to claim 3, wherein In parts by weight, the polyethylene terephthalate polymer includes one or more of polyethylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol and polyethylene terephthalate-1,4-cyclohexanedimethanol; and / or, the inorganic pore forming agent comprises one or more of alumina, silica, calcium carbonate, magnesium carbonate, calcium sulfate, barium sulfate, lead sulfate and zinc oxide; And / or, the D50 particle size of the inorganic pore-forming agent is 0.01 μm-2 μm.

5. The polyester composite film according to any one of claims 1 to 4, characterized in that, The polyester composite film has one or more of the following characteristics: (1) The thickness ratio of the first surface layer to the polyester base layer is (1-1.5): (3-4); (2) The thickness ratio of the second surface layer to the polyester base layer is (1-1.5): (3-4); (3) The polyester material includes one or more of polyethylene terephthalate, polyethylene terephthalate-1,4-cyclohexanedimethanol and polyethylene terephthalate-1,4-cyclohexanedimethanol.

6. A method for preparing a polyester composite film, characterized in that, The polyester composite film comprises: a polyester base layer and a first surface layer and a second surface layer respectively arranged on opposite sides of the polyester base layer. The preparation method comprises the following steps: The raw materials of the first surface layer, the polyester base layer and the second surface layer are independently mixed, and after melt slicing, a first pelletized material, a second pelletized material and a third pelletized material are prepared respectively; The first pelletized material, the second pelletized material and the third pelletized material are melt-mixed, co-extruded, and then stretched to prepare a polyester composite film substrate; The components of the polyester base layer include, by weight, 90 to 99 parts of polyester material and 1 to 10 parts of photoinduced strain material; the photoinduced strain material includes one or more of barium titanate ceramics, lead zirconate titanate ceramics, PI / CNTs photosensitive composite materials, PEEK / anthraquinone photosensitive composite materials, MIL-101 chromium metal organic frameworks, and UiO-66-NH2 / ZnO composite materials; the components of the first surface layer and the second surface layer include polyester terephthalate polymers; the transmittance of the first surface layer, the second surface layer, and the polyester material is independently 92% to 99%; The polyester composite film substrate is subjected to light irradiation treatment to prepare a polyester composite film.

7. The preparation method of the polyester composite film according to claim 6, characterized in that, The raw material components for preparing the first surface layer and the second surface layer independently include: 5 to 30 parts of an inorganic pore-forming agent and 70 to 95 parts of a polyterephthalate polymer; And / or, the preparation method comprises, before the light irradiation treatment: subjecting the polyester composite film substrate to an acid wash treatment to form a porous structure of the first surface layer and the second surface layer; And / or, the pickling step includes: pickling the polyester composite film substrate with an acid elution solvent; wherein the acid elution solvent includes one or more of hydrochloric acid, sulfuric acid, oxalic acid, citric acid, acetic acid and hydrofluoric acid.

8. The method for preparing a polyester composite film according to claim 6 or 7, characterized in that, The process parameters of the light irradiation treatment include: the wavelength of the irradiation light is 100nm~1000nm, and the irradiation time is 10s~10min.

9. The production method of the polyester composite film according to claim 8, characterized in that, The light irradiation treatment has one or more of the following characteristics: (1) The photoinduced strain material is barium titanate ceramic, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 240nm~260nm; (2) The photoinduced strain material is lead zirconate titanate ceramic, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 300nm~400nm; (3) The photoinduced strain material is a PI / CNTs photosensitive composite material, and the process parameters of the light irradiation treatment include: the type of irradiation light is infrared light, and the wavelength of the irradiation light is 800nm~1000nm; (4) The photoinduced strain material is a PEEK / anthraquinone photosensitive composite material, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 350nm~370nm; (5) The photoinduced strain material is a MIL-101 chromium metal organic framework, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 340nm~365nm; (6) The photoinduced strain material is a UiO-66-NH2 / ZnO composite material, and the process parameters of the light irradiation treatment include: the type of irradiation light is ultraviolet light, and the wavelength of the irradiation light is 300nm~400nm.

10. A method for preparing a composite current collector, characterized in that, The following steps are involved: A metal layer is deposited on at least one surface of the polyester composite film prepared by the preparation method according to any one of claims 6 to 9, Wherein, the time interval between the light irradiation treatment and the deposition of the metal layer is 0.1 minute to 30 minutes.

11. A composite current collector, characterized in that The composite current collector includes the polyester composite film according to any one of claims 1 to 5 and a metal layer provided on at least one surface of the polyester composite film.

12. The composite current collector according to claim 11, wherein The material of the metal layer includes one or more of aluminum and aluminum alloy; and / or, the thickness of the metal layer is 0.8 mm to 1.2 mm.

13. An electrode, characterized in that, It includes the composite current collector according to claim 11 or 12 or the composite current collector prepared by the preparation method according to claim 10.

14. A battery, characterized in that, It includes the electrode according to claim 13.

Citation Information

Patent Citations

  • Composite polyester film as well as preparation method and application thereof

    CN115320206A

  • Lead-free ceramic with rapid and efficient photoinduced shrinkage or elongation response and preparation method

    CN118851761A

  • Polymer composite film, composite current collector, preparation method of composite current collector, positive electrode and application of positive electrode

    CN119898103A

  • Swelling-resistant polyester composite film, and preparation method therefor and use thereof

    WO2024044897A1

  • Composite polyester film, and preparation method therefor and use thereof

    WO2024050722A1